Long-Term Efficacy of Clinical Hypnotherapy as a Stand-Alone Treatment for Generalized Anxiety Disorder (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The purpose of this study article is to explore the usefulness of therapeutic hypnotherapy as a treatment for Generalized Anxiety Disorder (GAD) with regard to its long-term effectiveness. Using a randomized controlled trial methodology, the research investigates the effects of clinical hypnotherapy in comparison to the outcomes of a control group that was provided with conventional treatment. In order to examine the long-term benefits of hypnotherapy on generalized anxiety disorder (GAD) symptoms, a number of different measures of anxiety intensity, quality of life, and functional impairment are performed at the beginning of the study, after treatment, and at follow-up intervals. The results show that hypnotherapy may play a role in the comprehensive care of generalized anxiety disorder (GAD), which is an important discovery.